SPE Extraction and TLC Identification of Tetracycline and Fluoroquinone in Surface Water - Bečić, Elvira; Imamović, Belma; Dedić, Mirza; Šober, Miroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Simultaneous identification of the antibiotics tetracycline, oxytetracycline, chlortetracycline, ciprofloxacin and enrofloxacin in surface water is reported. The method is based on solid-phase extraction (SPE), separation and identification by thin-layer chromatography (TLC). TLC separation was performed on TLC silica gel 60 F254 plates using a mobile phase system water/methanol/dichloromethane (6/35/59) (v/v). The plates were previously impregnated with 10% solution EDTA pH 9,0 and dried in a horizontal position for at least two hours at room temperature and then in an oven at 105°C 30 minutes shortly before use. Antibiotics were extracted on the OASIS HLB 6cc/500 mg cartridges. Aliquots of 10 μl of the water sample and reference solutions were applied to the plate. After development the plates were air dried and the chromatograms were visualized under UV light at λ = 254 nm and λ = 366 nm. Proposed method can be applied for screening of investigated antibiotics in water samples were antibiotic concentration is equal or higher than 5 μg/ml.